CONTRIBUTION OF SPLIT SQUAD JUMP EXERCISES, MEDICINE BALL OVERHEAD THROW EXERCISES, AND DUMBBLE WRIST EXERCISES AGAINST SMASHES IN VOLLEYBALL WOMEN'S ATHLETES CLUB MULIA IN 2020 - Wendy Rafli Silalahi; Ibrahim Wiyaka; M.Faisal Ansari Nst (Indonesia Sport Journal, 2022)
This study aims to determine the contribution of split squad jump exercises, medicine ball overhead throws, and dumbbell wirst exercises to smash in volleyball female athletes of the noble club in 2020. Statistical testing is assisted by the SPSS statistical program using descriptive tests, prerequisite tests for normality, linearity and tests. correlation and calculate the effective contribution and relative contribution of variables. The research sample was obtained by purposive sampling technique of 10 athletes. Before testing the hypothesis, they must pass the prerequisite test, namely, the normality test is the value > sig. 0.05 and the linearity test is greater than the 5% significance level, the regression correlation test shows that rcount > rtable. R table with the provisions of df = n-2 (10-2 = 8) in the two-way significance test of 0.05 is known to be 0.631. So that each independent variable with its dependent variable is significant. From the results of the prerequisite tests and statistical tests, the data obtained are SE 78.7% and SR 100%. This means that the contribution between the independent and dependent variables in this study is 78.7% while the remaining 21.3% is influenced by other variables outside the study. The results of this study indicate that (1) There is a Contribution of Split Squad Jump to Smash in Volleyball Putri Mulia Medan. (2) There is a Contribution of Medicine Ball Overhead Throw to the Smash in Putri Mulia Volleyball Ball in Medan. (3) There is a Dumbbell Wrist's Contribution to the Smash in the Putri Mulia Volleyball Ball in Medan. (4) There is a contribution of Split Squad Jump, Medicine Ball Overhead Throw and Dumbbell Wrist to Smash on Putri Mulia Volleyball Ball in Medan.Keywords : Split Squad Jump, Medicine Ball Overhead Throw, Dumbbell Wrist, Smash, Volleyball